2007
DOI: 10.1103/physrevb.75.144114
|View full text |Cite
|
Sign up to set email alerts
|

Origin of static friction and its relationship to adhesion at the atomic scale

Abstract: Using atomic scale interfaces consisting of slabs of the same materials, we study the relationship between adhesion and static friction. The work of separation, which is a measure of adhesion, and the spatial variation of the interface potential energy along the sliding direction are computed for both commensurate and incommensurate Al 2 O 3 /Al 2 O 3 interfaces, and incommensurate smooth and rough Al/ Al interfaces. These values are compared with the predicted static friction stress resulting from constant fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 23 publications
1
74
1
Order By: Relevance
“…Thus conducting experiments under controlled conditions and measuring macroscopic behaviors is a means to test and motivate models (see for example, [46] for friction in rock and [56,57] for metals). We tested the efficacy of the HSLS and the measurement system in the prototype machine to document different behaviors observed in parametric studies of mineralogy and rock composition by conducting preliminary double-direct-shear experiments on two different rock types (quartz sandstone versus granite) and different interface conditions (granite with and without a layer of wear material present).…”
Section: Use Of the Hsls To Investigate Seismic Frictional Slipmentioning
confidence: 99%
“…Thus conducting experiments under controlled conditions and measuring macroscopic behaviors is a means to test and motivate models (see for example, [46] for friction in rock and [56,57] for metals). We tested the efficacy of the HSLS and the measurement system in the prototype machine to document different behaviors observed in parametric studies of mineralogy and rock composition by conducting preliminary double-direct-shear experiments on two different rock types (quartz sandstone versus granite) and different interface conditions (granite with and without a layer of wear material present).…”
Section: Use Of the Hsls To Investigate Seismic Frictional Slipmentioning
confidence: 99%
“…In the FKT model this is accompanied by the emergence of a set of metastable states, but this phenomenon of emerging metastable states has not been directly investigated in more realistic three-dimensional systems. Moreover, using MD simulations of commensurate and incommensurate Al 2 O 3 surfaces and incommensurate Al surfaces Zhang et al 14 showed that the static friction does not depend on adhesion, and that increasing commensurability and roughness can raise the static friction.…”
Section: Introductionmentioning
confidence: 98%
“…where corresponds to the substrate particle number density (assuming an atomic radius of 0.2 nm, = 3.0×10 28 particles/m 3 ); ( ) is the energy coefficient,…”
Section: Model and Methodsmentioning
confidence: 99%
“…In particular, this type of systems have been extensively studied through SFA experiments by Israelachvilli, who, among other things, found that friction at the nano-scale could be correlated with the adhesion hysteresis phenomenon [6]. Furthermore, in order to achieve a fundamental understanding of these processes, efforts have and are still been made from both experimental [7][8][9][10][11][12][13][14][15] as well as theoretical and simulations points of view, such as through Molecular Dynamic Simulations (MDS) [16][17][18][19][20][21][22][23][24][25][26][27][28]. However, a satisfactory explanation of the friction mechanisms involved in this type of systems is still lacking, for example, with respect to the origin of phase transitions evidenced by the SS behavior and the effects of the adhesion hysteresis phenomenon.…”
Section: Introductionmentioning
confidence: 99%